Effectiveness of risk minimization measures for the use of cilostazol in United Kingdom, Spain, Sweden, and Germany. Issue 9 (25th July 2018) - Castellsague, Jordi; Poblador‐Plou, Beatriz; Giner‐Soriano, Maria; Linder, Marie; Scholle, Oliver; Calingaert, Brian; Bui, Christine; Arana, Alejandro; Laguna, Clara; Gonzalez‐Rubio, Francisca; Roso‐Llorach, Albert; Prados‐Torres, Alexandra; et al.
Abstract: Purpose: The purpose of the study is to evaluate the effectiveness of risk minimization measures—labeling changes and communication to health care professionals—recommended by the European Medicines Agency for use of cilostazol for the treatment of intermittent claudication in Europe. Methods: Observational study of cilostazol in The Health Improvement Network (United Kingdom), EpiChron Cohort (Spain), SIDIAP (Spain), Swedish National Databases, and GePaRD (Germany). Among new users of cilostazol, we compared the prevalence of conditions targeted by the risk minimization measures in the periods before (2002‐2012) and after (2014) implementation. Conditions evaluated were prevalence of smoking, cardiovascular conditions, concurrent use of ≥2 antiplatelet agents, concurrent use of potent CYP3A4/CYP2C19 inhibitors and high‐dose cilostazol, early monitoring of all users, and continuous monitoring of users at high cardiovascular risk. Results: We included 22 593 and 1821 new users of cilostazol before and after implementation of risk minimization measures, respectively. After implementation, the frequency of several conditions related to the labeling changes improved in all the study populations: prevalence of use decreased between 13% (EpiChron) and 57% (SIDIAP), frequency of cardiovascular contraindications decreased between 8% (GePaRD) and 84% (EpiChron), and concurrent use of high‐dose cilostazol and potent CYP3A4/CYP2C19 inhibitors decreased between 6% (Sweden) and 100% (EpiChron). The frequency of other conditions improved in most study populations, except smoking, which decreased only in EpiChron (48% reduction). Conclusions: This study indicates that the risk minimization measures implemented by the EMA for the use of cilostazol have been effective in all European countries studied, except for smoking cessation before initiating cilostazol, which remains an area of improvement.